2010
DOI: 10.1111/j.1471-4159.2010.07066.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid microelectrode measurements and the origin and regulation of extracellular glutamate in rat prefrontal cortex

Abstract: J. Neurochem. (2010) 115, 1608–1620. Abstract Glutamate in the prefrontal cortex (PFC) plays a significant role in several mental illnesses, including schizophrenia, addiction and anxiety. Previous studies on PFC glutamate‐mediated function have used techniques that raise questions on the neuronal versus astrocytic origin of glutamate. The present studies used enzyme‐based microelectrode arrays to monitor second‐by‐second resting glutamate levels in the PFC of awake rats. Locally applied drugs were employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 85 publications
(118 reference statements)
9
106
1
Order By: Relevance
“…This effect could be a compensatory response acting through presynaptic mGluR 2/3 autoreceptors (Rohde et al., 2012; Watanabe et al., 2011). In support of this explanation, we previously showed that resting glutamate levels are modulated with an mGluR 2/3 agonist and antagonist in freely moving animals (Hascup et al., 2010). Alternatively, there is also evidence that kindling may increase neuropeptide Y which has been shown to decrease resting glutamate levels in the hippocampus (Botterill, Guskjolen, Marks, Caruncho, & Kalynchuk, 2015; Klapstein & Colmers, 1997; Patrylo, van den Pol, Specer, & Williamson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be a compensatory response acting through presynaptic mGluR 2/3 autoreceptors (Rohde et al., 2012; Watanabe et al., 2011). In support of this explanation, we previously showed that resting glutamate levels are modulated with an mGluR 2/3 agonist and antagonist in freely moving animals (Hascup et al., 2010). Alternatively, there is also evidence that kindling may increase neuropeptide Y which has been shown to decrease resting glutamate levels in the hippocampus (Botterill, Guskjolen, Marks, Caruncho, & Kalynchuk, 2015; Klapstein & Colmers, 1997; Patrylo, van den Pol, Specer, & Williamson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This meant the sentinel sites could not record any converted glutamate but could record any electroactive interferents (at + 0.7 V vs a Ag/AgCl reference electrode) not repelled by Nafion. When the current recorded on the sentinel sites was subtracted from the current on the glutamate recording sites, the resulting signal represents the resting glutamate levels in brain tissue (Hascup et al, 2010;Burmeister et al, 2002;Burmeister and Gerhardt, 2001). …”
Section: Microelectrode Array Designmentioning
confidence: 99%
“…MEAs were calibrated to determine their sensitivity and selectivity against ascorbic acid as previously described (Hascup et al, 2010(Hascup et al, , 2009(Hascup et al, , 2008(Hascup et al, , 2006Nickell et al, 2005). Selectivity ratios for glutamate over ascorbic acid were calculated in addition to the slope (sensitivity), limit of detection (LOD), and linearity (R 2 ) for glutamate for all MEAs.…”
Section: Mea Calibrationmentioning
confidence: 99%
See 2 more Smart Citations